2020
DOI: 10.1140/epjc/s10052-020-7907-9
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the $$t\bar{t}$$ production cross-section and lepton differential distributions in $$e\mu $$ dilepton events from pp collisions at $$\sqrt{s}=13\,\text {TeV}$$ with the ATLAS detector

Abstract: The inclusive top quark pair (tt) production cross-section σ tt has been measured in proton-proton collisions at √ s = 13 TeV, using 36.1 fb −1 of data collected in 2015-2016 by the ATLAS experiment at the LHC. Using events with an opposite-charge eμ pair and b-tagged jets, the cross-section is measured to be: σ tt = 826.4 ± 3.6 (stat) ± 11.5 (syst) ± 15.7 (lumi) ±1.9 (beam) pb, where the uncertainties reflect the limited size of the data sample, experimental and theoretical systematic effects, the integrated … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 159 publications
1
47
0
Order By: Relevance
“…As the inclusive tt data are quite well described by predictions derived using these equations (see, e.g., Ref. [7]) and the results presented in Ref. [26] indicate that the uncertainty on g P is small in that kinematical range, we expect, as well, a small impact on our predictions associated with the choice of the diffractive parton distribution.…”
Section: Formalismsupporting
confidence: 58%
See 1 more Smart Citation
“…As the inclusive tt data are quite well described by predictions derived using these equations (see, e.g., Ref. [7]) and the results presented in Ref. [26] indicate that the uncertainty on g P is small in that kinematical range, we expect, as well, a small impact on our predictions associated with the choice of the diffractive parton distribution.…”
Section: Formalismsupporting
confidence: 58%
“…This expectation is directly related to the fact that the top quark couples to all gauge bosons and the Higgs boson, which implies that the top production is very sensitive to the presence of BSM phenomena. In addition, recent experimental results for the inclusive top pair production have demonstrated that this process can be used to measure the top mass in a well-defined scheme with high accuracy [5][6][7][8][9][10]. These results provide motivation for the study of the top pair production in diffractive processes, where the final state is cleaner than the typical inclusive one, where both incident protons fragment and a large number of particles are produced in addition to the top pair (for a review on diffraction see, e.g., Ref.…”
Section: Introductionmentioning
confidence: 99%
“…In this section we compare predictions for one-and two-dimensional leptonic differential distributions based on inclusive selection (in the sense of section 3) with ATLAS measurements [67]. The fiducial phase-space of the ATLAS analysis has only lepton requirements and no explicit cuts on jets.…”
Section: Leptonic Differential Distributions With Inclusive Selectionmentioning
confidence: 99%
“…The fiducial phase-space of the ATLAS analysis has only lepton requirements and no explicit cuts on jets. Two different measurements are presented in the ATLAS publication [67]: one that includes top-quark decays into τ -leptons and one which does not. In this work we do not consider decays to τ leptons and therefore exclusively compare to the τ -less measurement.…”
Section: Leptonic Differential Distributions With Inclusive Selectionmentioning
confidence: 99%
“…The measurements of these observables allow better understanding of correlations between different aspects of the tt system kinematics. These combinations are useful for extracting information about PDFs and measuring the top-quark pole mass from the differential cross-section measurements [78,79]. The combinations considered are:…”
Section: Double-differential Measurementsmentioning
confidence: 99%